The Application of NTAUTO in the 1000MW Ultra-supercritical Units - BAO Zhen; ZOU AI Hong; HUANG Huanpao; QIU Zhongchang; XIA Ming; PAN Gang (Institute of Advanced Engineering and Science, 2013)
NTAUTO is an auto-configuration software, which is developed by department of technology of Beijing GuoDianZhiShen Control Technology Co., Ltd.,. The configuration software has been applied in the configuration of 1000MW ultra-supercritical units. The automated configuration technology is the advanced technology of Beijing GuoDianZhiShen Control Technology Co., Ltd through years of accumulated technology in thermal power control field. It makes full use of computercontrol and CRT to provide a configuration solution of I/O database, SAMA control sheet, and the man-machine interface. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2378